Influence of tert gene expression, telomerase activity and telomere length in relation to imatinib mesylate resistance in Malaysian chronic myeloid leukaemia patients - Shamshudin, Wati @ Hayati Mohd (2020)
Chronic myeloid leukaemia (CML) is a myeloproliferative neoplasm diagnosed by the presence of the BCR-ABL fusion gene which produces a tyrosine kinase to signal a proliferation of white blood cells. The introduction of imatinib mesylate in early 2000, has dramatically increased the survival of affected patients and changed the disease management. However, failure to completely eradicate leukaemic cells and the escape of these cells from previous control has led to an intensive search for the mechanisms of resistance and subsequent treatments by which to overcome the resistance. Meanwhile, telomerase regulation and telomere maintenance are the critical factors in cell proliferation and survival which plays important roles in development of cancers. Considering telomerase as an important component in cell regulations, it is postulated that telomerase might be one of the oncogenesis mechanism in CML development and might contribute in the resistance mechanism of imatinib mesylate. A total of 98 CML patients were recruited from four collaborated hospitals over the country which are Hospital Pulau Pinang, Hospital Sultanah Aminah, Hospital Raja Permaisuri Bainun and Pusat Perubatan Universiti Kebangsaan Malaysia. Samples were also collected from Hospital USM which is the research center for this study. CML patients treated with imatinib were enrolled into this study and grouped as good response and resistance according to response of the imatinib mesylate treatment. Sixty-six of patients with good response at the beginning of samples collection and 32 patients with resistance response were managed to recruited. However, only 90 samples were able to proceed with DNA and RNA extraction while 79 samples were successfully applied for protein extraction due to poor quality of samples obtained. Range of age was between 71 to 77 years old and represented of main ethnicity in Malaysia which were Malay, Chinese and Indian. The analysis of hTERT expression level, telomerase activity and length of telomere were performed. The up regulated of hTERT expression and the presence of telomerase activity were found up to 90% in CML patients recruited in this study regardless of response group. This indicated that telomerase regulations as the indicator of cancer events in CML. However the telomerase regulations might not directly influenced the response and resistance group of treated patients. Comparison between good response and resistance group showed no significant difference (p=0.463 in hTERT expression and and p=0.961 in telomerase activity). Comparison of telomere length in both groups were also showed no significant difference (p=0.228). The findings indicated that hTERT expression, telomerase activity and telomere length may not directly influnced the resistance to imatinib mesylate treatment. To the best of our knowledge, there is no study comparing the expression and activity of telomerase in group of difference response to imatinib treatment in CML patients. This could consider that hTERT and the activitiy of telomerese together with telomere length in CML might have different contributions in resistance development compared to other solid tumours. Further more, investigations with a larger number of samples is warranted to confirm the potential influence of the telomerase and telomere components in the leukaemogenesis and imatinib resistance in Malaysian CML patients.